Poor Families' Dependence on Government Social Assistance Programs in Stabat Lama Barat Village - Rossa Meilani Putri; M. Nazaruddin; Nirzalin; Cut Rizka Al Usrah; Alwi (Program Magister Administrasi Publik, 2025)
This research aims to determine the Dependence of Poor Families On Government Social Assistance Programs (Case Study in Mekar Sari Hamlet, Stabat Lama Barat Village, Wampu District, Langkat Regency). The focus of this study includes social and economic dependence as well as the factors that cause poor families to rely on social assistance. This research uses a qualitative method with a descriptive approach to comprehensively describe the social reality of the beneficiaries. The theory used is the Habitus theory proposed by Pierre Bourdieu. The results show that community dependence occurs not only in the economic aspect but also extends to social and structural realms. Social assistance programs such as PKH, BPNT, BLT-DD, replacing the role of work productivity and forming a passive mindset. The factors causing dependency include job and income instability, low levels of education and skills, the absence of sustainable empowerment programs, and consumer-oriented aid policies. The impact of dependence on social assistance makes people have a dependent attitude by maintaining poor status in order to continue receiving assistance. Analysis through the theory of Habitus shows that the lived experience in conditions of persistent scarcity creates habits and passive mindsets that are passed down through generations. This habitus is difficult to change without strong structural intervention from the government through comprehensive and sustainable community empowerment programs.